The Influence of Convenience, Benefits, and Security on Students' Interest in Using the DANA E-Wallet in the Context of Digital Literacy - Siti Shahlatul Mukaromah; Octaviana Arisinta (Global Action and Education for Society, 2025)
Rapid advancements in digital technology have shifted consumer behavior toward cashless transactions, making digital wallets increasingly popular, especially among students. DANA is one of the most sought-after digital wallets. This research aims to determine the influence of convenience, benefits, and security variables on the interest in using the DANA e-wallet among students at STKIP PGRI Bangkalan. This quantitative study uses a non-probability sample and involves 40 student respondents who are active users of the DANA application. Data was collected thru online questionnaires and analyzed using multiple linear regression via IBM SPSS version 25. The results show that the variables of ease, benefits, and security have a significant influence, both partially and simultaneously, on students' interest in using DANA. Among the three, the benefits variable has the most dominant influence, followed by security and ease. With a coefficient of determination (R²) value of 0.794, it can be seen that the third variable explains 79.4% of the variation in usage interest. Meanwhile, the remaining 20.6% was influenced by other factors not included in this study. This finding indicates that improving ease of use, tangible benefits, and data security features is crucial in increasing user engagement and interest in digital wallet services, particularly among students.